Metabolites of Siberian Raspberries: LC-MS Profile, Seasonal Variation, Antioxidant Activity and, Thermal Stability of Rubus matsumuranus Phenolome - Nina I. Kashchenko (MDPI AG, 2021)
Rubus matsumuranus H. Lev. & Vaniot, a famous Siberian shrub of the Rosaceae family, is used in the folk medicine of nomads (Buryats, Yakuts, Soyots, and Mongols) as a remedy for the treatment of diseases of the respiratory and hepatobiliary systems. The lack of scientific information on R. matsumuranus leaves contributed to the investigation of the metabolomic profile and biological activity of this plant. In this study, metabolites of R. matsumuranus leaves in three stages (active growth, flowering, and fruiting) were characterised using high-performance liquid chromatography with photodiode array and electrospray ionisation triple quadrupole mass spectrometric detection (HPLC-PDA-ESI-tQ-MS). In total, 63 compounds were identified, including gallic acid derivatives, hydroxycinnamates, catechins, procyanidins, flavonols, and ellagitannins. Lambertianin C (57.11 mg/g of dry weight, DW), miquelianin (39.63 mg/g DW), and kaempferol-3-O-glucuronide (31.18 mg/g DW) were the major compounds in R. matsumuranus leaves. As a result of the HPLC-PDA-based assay to determine the antioxidant activity, it was revealed that lambertianin A, sanguiin H6, lambertianin C, and sanguiin H11 were effective scavengers of free radicals (2,2-diphenyl-1-picrylhydrazyl, DPPH•) and possessed Fe2+-chelating activity. After an investigation of the phenolic content in infusions and decoctions obtained by extraction with water at different temperatures, it was revealed that a hot infusion (80 °C) is a phenolic-rich preparation of R. matsumuranus leaves. Our research suggests that R. matsumuranus leaves are a rich source of phenolic compounds with high antioxidant properties and that this could be a prospective plant for new functional products.